Смысловой анализ текстов (Библиосфера, 2010)
The review of approaches to the semantic analysis of texts is presented. The author's term and approach «texts sense analysis» is offered. It includes «consepts» of different levels, including situational, connected not only with scientific, but also business, reference texts, publications on leisure. The methodical scheme of this approach use in the bibliograph-analyst activity is given.